THE ESSENCE OF NOTARY LEGAL OFFERING IN WEST LAND RIGHTS DISPUTES (EIGENDOM VERKLARING) - Andi Evy Anggraeni Tr (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Law has a goal that is to encourage social change for the better through legal certainty. The land ownership system in Indonesia during the Dutch East Indies era was subject to the Agrarische Wet 1870 (Stbd 1870: 55). This type of research is Normative Empirical, with the starting point of research on Western land rights (Eigendom) which have been declared invalid but are still used as a legal basis for civil lawsuits in court, with primary data as supporting secondary data. From one of the inkrach cases, it showed the district court judge and cassation had wrongly applied the law, namely the plaintiff used old evidence in the form of Eigendom Number 9703 which was former Eigendom land owned by Raden Harsa Nata Sastra Nagara since December 27, 1907 and was not a valid evidence . It is important that the function of legal counseling for Notaries as in Article 15 paragraph (2) letter e of the UUJN. Legal education activities are one of the socializations to illustrate how justice is. National law cannot guarantee the realization of this justice. The function of legal counseling is also a preventive, corrective, presevative and developmental measure